The Application of Law Towards The Right to Health Services for Community Inmates (Study of Class II A Binjai Prison) - Andi Gultom; Abdul Rahman Maulana Siregar; Suci Ramadani (Journal Evidence Of Law, 2025)
Correctional inmates are members of society who, unable to adapt to life in other communities, commit violations that require isolation and serve their sentences. During this process, they will be placed in a correctional institution (LAPAS). Law No. 22 of 2022 concerning Corrections regulates the right to health services for all inmates. This is a crucial factor for inmates in facilitating all correctional activities in the prison. The research was conducted in Binjai City, specifically at the Class II A Binjai Correctional Institution (Lapas) Office. This study used an empirical juridical approach. Data obtained in the field were presented descriptively using an empirical normative approach.This study aimed to determine the provision of health services to inmates at the Class II A Binjai Prison and the obstacles faced in providing these services to inmates at the Class II A Binjai Prison. Based on the author's research findings, the health services provided are in accordance with applicable laws and regulations. However, overcapacity has resulted in suboptimal services. Obstacles faced in providing health services to inmates come from within the inmates themselves, due to the large number of inmates not yet registered as BPJS Kesehatan holders, a lack of awareness of administrative regulations, and overcapacity, which results in suboptimal health services